Efektifitas Pemberian Suplementasi Zinc dalam Mengatasi Diare pada Anak: Literature Review - Meivita Dewi Purnamasari; Devi Oktavia Anisa (Journal of Bionursing, 2019)
Introduction. Diarrhea is one of the leading causes of death in children. Diarrhea is a disease characterized by increasing frequency defecation of more than three times a day with a change in stool consistency to liquid. When diarrhea occurs fluid and electrolyte loss for that effort is done by providing zinc supplementation.Objective. To identify the effectiveness of zinc supplementation in overcoming diarrhea in children.Method. journal article search is done by using electronic tool with internet connection like some database, that is: Pubmed, Google Scholar. Keywords used are "Zinc", "Zinc Supplementation ", "Diarrhea", “Children”; so get 3 journal articles from 2012 to 2017 for the review.Results. Nursing interventions in administering zinc supplementation to address diarrhea are categorized as safe and effective interventions in reducing the severity of diarrhea in children.Discussion. Increasing the frequency of defecation causes the body to lose fluids by improving the condition by providing zinc supplementation to prevent diarrhea.Conclusion: zinc supplementation is effective in diarrhea in children.